Natural science from the worldview of the Qur'an: an introduction - volume 2 - Zubir, Nazira; Hassan, Nur Jannah; Mohd. Yusof, Mohd Isa; Husin, Abu Hasan; Hassan, Mohd Kamal (Institut Terjemahan & Buku Malaysia (ITBM), 2018)
This book, the second of a three-volume work in natural science for secondary school students, consists of three chapters. Energy is that which stirs our world to life and is so much in demand today. "energy, dynamics and motion" is thus the theme of CHAPTER 1, which explores the various forms and sources of energy created by Allah the most gracious, the different technologies available on how best to harness them and the problems associated with these. The vehemently debated nuclear energy is allotted a special focus keeping in view of all the implications, responsibilities and precautions. With energy, there is force, which in turn sets matter in motion with or without us realising it. The chapter elaborates on dynamics, support in the structures of organisms and the physiology of their movements, followed by an exploration of the physics of motion.